On the age of the most ancient pegmatites of the Svecofennian block in the Northern Ladoga region (SE of the Fennoscandian shield) (Proceedings of Voronezh State University. Series: Geology, 2023)
Introduction: In the Svecofennian block of the Northern Ladoga region, where the Early Proterozoic metamorphic complex is developed, U-Pb dating of monazite revealed the most ancient granite pegmatites for this region, marking the completion of the active phase of magmatic and metamorphic development of the structures of the region. Previous studies of the svecofennides of the Northern Ladoga region estimated the main phase of endogenic activity in the region at an age interval of 1881–1860 Ma. These estimates were based on U-Pb dating of zircon and monazite from various granitoids and associated pegmatitic veins. Methods: To determine the age of the pegmatite vein, a U-Pb geochronological study (ID-TIMS) was carried out. Results and discussion: The identified age of the pegmatitic vein we studied (1869 ± 5 Ma) turned out to be somewhat older than the previously known ages of pegmatites and granites (1858–1860 Ma), which further narrows the time range of intense plutono-metamorphic activities in the region. A similar very short duration of the active phase of plutono-metamorphic events (ca. 15 Ma) was previously revealed when dating syn- and post-kinematic granites from the Central Finnish granitoid complex, located northwest of the Northern Ladoga region. Conclusion: The coincidence of the duration of endogenous activity in the southern domain of the Ladoga region with the duration established for the Central Finnish granitoid complex makes it possible to make closer and more accurate correlations when analyzing scenarios for the tectonic development of Proterozoic rocks in these adjacent regions.
Keywords: U-Pb dating; monazite; pegmatite; granite; Svecofennian complex